2023
DOI: 10.1186/s13195-022-01158-6
|View full text |Cite|
|
Sign up to set email alerts
|

Walking pace, handgrip strength, age, APOE genotypes, and new-onset dementia: the UK Biobank prospective cohort study

Abstract: Background The independent and additive associations of walking pace and grip strength on dementia risk and the potential modifying effects of age, APOE phenotypes, and other dementia risk factors on the walking pace and dementia relationships demand further clarification. We aimed to investigate the independent and additive relationships of walking pace and handgrip strength on the risk of new-onset dementia and examine the potentially modifying effects of age, APOE phenotypes, lifestyle facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 45 publications
(47 reference statements)
0
3
0
Order By: Relevance
“…It is of interest to notice that a recent prospective cohort study, with 340,212 participants, suggests an association of an absolute 5 kg increment of grip strength with a lower risk of AD (HR 0.874) [19]. Another prospective cohort study, with 495,700 participants with a median 12 years followup, demonstrates that walking pace is inversely associated with new-onset dementia, particularly in young participants with lower APOEε4 dosage [20]. However, the mechanisms underlying the association between cognitive impairment and sarcopenia appear to be complicated.…”
Section: Ad Association With Sarcopeniamentioning
confidence: 99%
“…It is of interest to notice that a recent prospective cohort study, with 340,212 participants, suggests an association of an absolute 5 kg increment of grip strength with a lower risk of AD (HR 0.874) [19]. Another prospective cohort study, with 495,700 participants with a median 12 years followup, demonstrates that walking pace is inversely associated with new-onset dementia, particularly in young participants with lower APOEε4 dosage [20]. However, the mechanisms underlying the association between cognitive impairment and sarcopenia appear to be complicated.…”
Section: Ad Association With Sarcopeniamentioning
confidence: 99%
“…Therefore, a combination of the two may be more relevant to health outcomes than use alone. 14,15 However, to date, the combined effect of grip strength and walking pace on the risk of PD has not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, from a physiological perspective, grip strength and walking pace may reflect different underlying physiological processes: Grip strength is more likely a measure of contraction strength, while walking pace integrates strength with other processes (e.g., balance and coordination). Therefore, a combination of the two may be more relevant to health outcomes than use alone 14,15 . However, to date, the combined effect of grip strength and walking pace on the risk of PD has not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Handgrip strength (HGS) is an important indicator of physical function, and a biological marker of aging throughout the lifespan (4). Extensive studies have consistently demonstrated a robust correlation between low HGS and a range of adverse health outcomes, including hip fracture, nutrition deficiencies, new-onset chronic diseases and mortality risk (5)(6)(7)(8)(9). The measurement of HGS involves a simple and highly reproducible procedure utilizing a portable and relatively low-cost dynamometer, so it can be easily implemented in regions with limited advanced medical equipment (10).…”
Section: Introductionmentioning
confidence: 99%